النقد الثقافي ما بعد البنيوي، وتحولاته النظرية والتطبيقية في كتاب (نقد النقد الثقافي... للدكتور عبد العظيم السلطاني) - Abdullah Ahmed, Assist. Prof. Dr. Abdul Rahman (Basra studies journal, 2025)
The study aims to verify the validity of the hypotheses proposed by Dr. Abdul-Azeem Al-Sultani in his book Critique of Cultural Criticism, concerning the necessity of branching poststructuralist cultural criticism into distinct categories: literary cultural criticism, research criticism, critique of cultural studies, and critique of cultural criticism itself. This effort seeks to establish the foundation for cultural theory, question its concepts, and regulate its epistemological principles within both Western and Arab contexts.The study attempts to address these questions by uncovering their origins, references, and their ability to sustain relevance in Arab critical discourse, emphasizing the practical dimension. In the final two chapters of the book, Al-Sultani presents an applied perspective that aligns with the preceding arguments outlined in the introduction and subsequent sections. The cultural reading of this significant work concludes that broadening the theoretical scope through branching and specialization leads to intellectual and epistemological centralization and stabilization—a stance opposed by postmodernist inclinations.